(untitled) (Law and Safety, 2022)
Based on a systematic analysis of the explanations of the highest judicial bodies of Ukraine and civil law on the application of the statute of limitations to a negatory action, the problem clarifications of the Supreme Court was identified (for example, this applies to the conclusion, made by the Grand Chamber of the Supreme Court in case № 653/1096/16-ц of 4 July 2018), which do not comply with the letter of the law, but must be taken into account by the courts when applying these rules of law in in similar cases. It is concluded that acts of judicial interpretation of the Supreme Court, which do not comply with the expression “prescribed by law” and “in accordance with the law”, become the regulator of civil relations, as according to law have binding procedural force before their application in similar cases. It was found that the essence of such a decision contradicts the concept of the Central Committee of Ukraine and the Constitution of Ukraine, as a judicial act, according to the current concept of civil law of Ukraine is not a source of regulation of civil relations. In this regard, the author emphasizes that our legal system is vulnerable to violations of the rights and interests of participants in civil relations, in particular when the decision containing the conclusions of the Supreme Court of the state becomes the regulator of civil relations. As a result, this leads to probable cases when the goals of civil (Part 1 of Article 2 of the Civil Procedural Code of Ukraine) and commercial (Part 1 of Article 2 of the Commercial and Procedural Code of Ukraine) judicial proceedings will not be achieved. In view of this, the author proposes to establish in civil and commercial procedural law a mechanism for reviewing the final decision of the Supreme Court, in particular in cases when the assessment by such a court of facts and legal norms causes education legal position (legal standard), which in fact acquires the character of a quasi-source of law.